2016
DOI: 10.1242/jeb.143644
|View full text |Cite|
|
Sign up to set email alerts
|

Navigating under sea ice promotes rapid maturation of diving physiology and performance in beluga whales

Abstract: Little is known about the postnatal development of the physiological characteristics that support breath-hold in cetaceans, despite their need to swim and dive at birth. Arctic species have the additional demand of avoiding entrapment while navigating under sea ice, where breathing holes are patchily distributed and ephemeral. This is the first investigation of the ontogeny of the biochemistry of the locomotor muscle in a year-round Arctic-dwelling cetacean (beluga whale, Delphinapterus leucas). Compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 75 publications
3
19
2
Order By: Relevance
“…However, recent research on pigeon guillemot (Cepphus columba; Haggblom et al, 1988), penguins (Weber et al, 1974;Ponganis et al, 1999;Noren et al, 2001), sea otter (Enhydra lutris nereis; Thometz et al, 2015), pinnipeds (seals, sea lions and walruses; P. H. Thorson, Development of diving in the northern elephant seal, PhD thesis, University of California, Santa Cruz, 1993;Noren et al, 2005Noren et al, , 2015Burns et al, 2005Burns et al, , 2007Richmond et al, 2006;Fowler et al, 2007;Weise and Costa, 2007;Kanatous et al, 2008;Lestyk et al, 2009;Verrier et al, 2011) and cetaceans (whales and dolphins; Dolar et al, 1999;Etnier et al, 2004;Noren, 2004;Noren et al, 2001Noren et al, , 2014Cartwright et al, 2016;Noren and Suydam, 2016; B. P. Velten, A comparative study of the locomotor muscle of extreme deep-diving cetaceans, MSc thesis, University of North Carolina, Wilmington, 2012) have shown that a period of postnatal development is required in order to achieve mature muscle myoglobin content and muscle buffering capacity after birth. It was anticipated that the immediate demands of hypoxia should promote rapid muscle maturation in cetaceans since they are born directly into the ocean, compared with pinnipeds that are born on land and typically spend several months to years on land before foraging on their own (for reviews, see Noren et al, 2005Noren et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, recent research on pigeon guillemot (Cepphus columba; Haggblom et al, 1988), penguins (Weber et al, 1974;Ponganis et al, 1999;Noren et al, 2001), sea otter (Enhydra lutris nereis; Thometz et al, 2015), pinnipeds (seals, sea lions and walruses; P. H. Thorson, Development of diving in the northern elephant seal, PhD thesis, University of California, Santa Cruz, 1993;Noren et al, 2005Noren et al, , 2015Burns et al, 2005Burns et al, , 2007Richmond et al, 2006;Fowler et al, 2007;Weise and Costa, 2007;Kanatous et al, 2008;Lestyk et al, 2009;Verrier et al, 2011) and cetaceans (whales and dolphins; Dolar et al, 1999;Etnier et al, 2004;Noren, 2004;Noren et al, 2001Noren et al, , 2014Cartwright et al, 2016;Noren and Suydam, 2016; B. P. Velten, A comparative study of the locomotor muscle of extreme deep-diving cetaceans, MSc thesis, University of North Carolina, Wilmington, 2012) have shown that a period of postnatal development is required in order to achieve mature muscle myoglobin content and muscle buffering capacity after birth. It was anticipated that the immediate demands of hypoxia should promote rapid muscle maturation in cetaceans since they are born directly into the ocean, compared with pinnipeds that are born on land and typically spend several months to years on land before foraging on their own (for reviews, see Noren et al, 2005Noren et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…It was anticipated that the immediate demands of hypoxia should promote rapid muscle maturation in cetaceans since they are born directly into the ocean, compared with pinnipeds that are born on land and typically spend several months to years on land before foraging on their own (for reviews, see Noren et al, 2005Noren et al, , 2015. Yet it was discovered that cetaceans can take approximately 1-3 years after birth to achieve mature myoglobin content (Dolar et al, 1999;Noren et al, 2001Noren et al, , 2014Noren and Suydam, 2016) and buffering capacity (Noren, 2004;Noren et al, 2014;Noren and Suydam, 2016) in the muscle.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations